Aproximações culturais e conflitos sociais em torno da imagem do Bom Jesus da Cana Verde: entre o passado ibérico e as disputas no Brasil - Lino, Anderson (2016)
This dissertation focus on the struggles for the monopoly of power based on an image that represents the Senhor Bom Jesus da Cana Verde. Established in the city of Siqueira Campos, in the region of the Old North of the Paraná State, Brazil, the image is the result of conflicts that took place in 1933, in a village called Bom Jesus dos Pintos. This research also seeks to understand the cultural similarities between the images that represent the Senhor Jesus do Sacro Monte (Braga), the Senhor Jesus da Pedra (Óbidos), and the Senhor Bom Jesus de Bouças (Matosinhos) – all three located in Portugal –, which engendered the cults practiced in Brazil throughout the 18th century. It is the history of conflicts, of social movements, and of new political and religious arrangements, in moments in which traditions were broken and the delight with the world and the raison d’état were no more. On that account, it was vital to this work to analyse the syncretism of the religious phenomenon and, at the same time, the concepts of progress and development, which introduced a “modernity” in that region by gathering experiences and expectations around a baroque drama, concealing the conflicts between the “civilized” and the “Kaingang” Indians; between, outlaws, brigands, sharecroppers and large landowners